2019
DOI: 10.3390/w11020377
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Excitation-Emission Spectroscopy: An Analytical Technique to Monitor Drugs of Addiction in Wastewater

Abstract: Emerging contaminants of concern have become a serious issue for the scientific community and society more broadly in recent years due to their increasingly widespread environmental distribution and largely unknown environmental and human health impacts. This study aimed to explore the use of fluorescence excitation-emission (F-EEM) spectroscopy as an alternative analytical method to evaluate the presence of key drugs of addiction (benzoylecgonine, methamphetamine, MDMA, codeine and morphine) in wastewater tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Another interesting phenomenon was a local (not occurring at all dates) increase in FI in the region of ~300 nm/450 nm (ex/em). These changes could reflect newly formed, low-molecular HAs, which may have resulted from the activity of microorganisms [ 68 , 69 ]. The spectral location of this maximum can also be attributed to molecules more similar to fulvic acids [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another interesting phenomenon was a local (not occurring at all dates) increase in FI in the region of ~300 nm/450 nm (ex/em). These changes could reflect newly formed, low-molecular HAs, which may have resulted from the activity of microorganisms [ 68 , 69 ]. The spectral location of this maximum can also be attributed to molecules more similar to fulvic acids [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three-dimensional fluorescence excitation-emission matrices (EEM) measure the intensity of the light emitted by a sample over the entire range of scanned excitation and emission wavelengths. EEM analysis has been increasingly adopted in fields including drugs in wastewater [11], oil pollutants [12,13] and foods [8][9][10]14], to name just a few. Previous studies have shown the possibility of using steady-state multidimensional fluorescence spectroscopy in studies of various wines [15][16][17][18][19], brandies and wine distillates [20] and other beverages including beer [21].…”
Section: Multidimensional Fluorescence Spectroscopymentioning
confidence: 99%
“…The results indicated that COD concentration was positively correlated with humic-like substances. Several studies [20,21] have sought to investigate the potential of fluorescence excitation-emission (F-EEM) spectroscopy as an alternative analytical method for assessing the relationship between the presence of crucial drugs of addiction, ammonia, and pH with PARAFAC components. However, the correlation analysis techniques used in the above studies were RDA, canonical correlation, or linear correlation analysis methods.…”
Section: Introductionmentioning
confidence: 99%